FRI0228 Paradoxical Articular Manifestations in Inflammatory Bowel Diseases Patients Treated by Anti-TNF. (9th June 2015) - Lasselin, P.; Thiebault, H.; Goeb, V.; Dupas, J.L.; Fumery, M.
Abstract : Background: Articular manifestations are the most common extra-intestinal manifestations associated to inflammatory bowel diseases (IBD). They are named "paradoxical" when they occur during treatment, notably anti-TNF drugs, that are expected to prevent or at least treat them. Objectives: The aim of this study was to assess the frequency, the characteristics and the associated factors of paradoxical articular manifestations during anti-TNF treatment for IBD. Methods: In this prospective single-center study, a rheumatological examination was systematically proposed to all IBD patients treated with infliximab (IFX) or adalimumab (ADA) to assess the prevalence of articular manifestations and distinguish those related to IBD treatment of those associated with IBD. Paradoxical manifestations were defined by the occurrence of articular manifestations (excluding induced-lupus and hypersensitivity reaction) during anti-TNF therapy in a patient in IBD intestinal remission. Dosage of biological inflammatory (WBC, ESR, CRP) immunological markers (immunoglobulins, anti-nuclear antibody (Ab), anti-DNA Ab, anti-CCP Ab, complement factor, rheumatoid factor, ASCA) and HLA-B27 allele and through serum IFX and anti-IFX Ab were systematically performed. Results: Between May 2013 to April 2014, 79 patients with Crohn's disease (CD) and 20 ulcerative colitis (UC) treated with IFX (n=80) or ADA (n=19) were included. Immunosuppressors (azathioprine/methotrexate) were associated in 12% of cases. Articular manifestations were observed in 50 (62%) patients treated by IFX and 12 (63%) patients treated by ADA. Twelve percent (n=12) were considered associated to IBD and 16% (n=16) associated to anti-TNF therapy. Among patients with articular manifestations associated to anti-TNF therapy, we identified 12% (n=12) of paradoxical effects, 2% (n=2) of induced lupus and 2% (n=2) of hypersensitivity reaction. Among the 12 patients with paradoxical effects during IFX (n=9) or ADA (n=3) therapy, 11 were treated for CD and presented peripheral arthritis; 3 patients presented a spondyloarthropathy. Paradoxical cutaneous manifestations (psoriasis) were associated in 25% of cases. The median duration of anti-TNF therapy was 47 months (Q1=30-Q3=77). No patient has discontinued anti-TNF because of the articular manifestations. Three patients were treated with methotrexate. No clinical or biological factors were associated with the occurrence of paradoxical manifestations. Conclusions: Paradoxical articular manifestations in IBD patients treated by anti-TNF are common, affecting more than 10% of patients. These events are generally mild and not followed by the discontinuation of anti-TNF drugs Disclosure of Interest: None declared